O raciocínio geográfico: mobilizações intelectuais na interpretação de situações geográficas - Patrícia Assis da Silva (2021)
This work searched to approach the geographical reasoning mobilize by the teacher when interpreting a given geographical situation. Geographical reasoning is a way of thinking that is exclusive to geographic science and allows the interpretation of geographical situations. The study, developed with geography teachers from the basic network, focuses on the investigation of the knowledge operated by geography teachers when interpreting a given geographical situation, mobilizing this reasoning. The Data were collected using two instruments. The first instrument was applied to nine subjects and consisted of a didactic sequence worked during the VI Geographic Interpretations Workshop: spatialities and teaching practices, offered by GEPEGEO. The second instrument was built based on the ideia of a projective interview and was worked with tree subjects. Both instrument were articulated by a question about a given geographical situation. The analysis of the data took place in dialogue with the principles of learning developed by Bloom et al. (1956) and theoretical references of the geography teaching (ROQUE ASCENÇÃO, VALADÃO, 2016, 2017a, 2017b). The teachers use concepts, but not always mobilize the concepts used. Teachers who operated with the cognitive domain categories of Bloom et al. (1956) listed in the activities and/or questions, also approached the mobilization of geographic reasoning. The more teachers appropriated the materials, the closer they came to scientific knowledge and the mobilization of geographical reasoning. Geographical reasoning is a mental and particular operation of the individual, however, the initial training of the geography teacher must provide subsidies and tools for the subject to learn to operate with this reasoning to interpret geographic situations and understand the spatiality of the phenomenon.